To the Reading of the Greek Novgorod Birchbark Letter No. 552 - Aleksei Shchavelev (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения)
The paper proposes a clarification of the reading of the only birchbark letter No. 552 written in Greek. The correct (in general) reading of this text, proposed in the publication of the letter and accepted in the historiography, nevertheless raises a number of questions that make it reconsidered by the methods of paleography and communication aim interpretation. According to the results of the analysis, it is assumed that letter No. 552 is a memorable note by the icon painter Olisej Petroviм Greмin, who indicated that on the icon it was necessary to paint St. Mercurius precisely in the image of a holy warrior, but not in the image of a martyr. All the words in this mini-text stand in the nominative case; it uses three ligatures and two end-of-word contractions. Judging by the brevity combined with the elegance of the execution, this entry “for myself” is a Greek autograph of the Olisej Greìin.